-3(8p+4)-2(1-23p)=3(6+7p)

Simple and best practice solution for -3(8p+4)-2(1-23p)=3(6+7p) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(8p+4)-2(1-23p)=3(6+7p) equation:


Simplifying
-3(8p + 4) + -2(1 + -23p) = 3(6 + 7p)

Reorder the terms:
-3(4 + 8p) + -2(1 + -23p) = 3(6 + 7p)
(4 * -3 + 8p * -3) + -2(1 + -23p) = 3(6 + 7p)
(-12 + -24p) + -2(1 + -23p) = 3(6 + 7p)
-12 + -24p + (1 * -2 + -23p * -2) = 3(6 + 7p)
-12 + -24p + (-2 + 46p) = 3(6 + 7p)

Reorder the terms:
-12 + -2 + -24p + 46p = 3(6 + 7p)

Combine like terms: -12 + -2 = -14
-14 + -24p + 46p = 3(6 + 7p)

Combine like terms: -24p + 46p = 22p
-14 + 22p = 3(6 + 7p)
-14 + 22p = (6 * 3 + 7p * 3)
-14 + 22p = (18 + 21p)

Solving
-14 + 22p = 18 + 21p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-21p' to each side of the equation.
-14 + 22p + -21p = 18 + 21p + -21p

Combine like terms: 22p + -21p = 1p
-14 + 1p = 18 + 21p + -21p

Combine like terms: 21p + -21p = 0
-14 + 1p = 18 + 0
-14 + 1p = 18

Add '14' to each side of the equation.
-14 + 14 + 1p = 18 + 14

Combine like terms: -14 + 14 = 0
0 + 1p = 18 + 14
1p = 18 + 14

Combine like terms: 18 + 14 = 32
1p = 32

Divide each side by '1'.
p = 32

Simplifying
p = 32

See similar equations:

| (2-2y)*((2-x)/2) | | x=1.01255555555555 | | 2-2y+2y-2=0 | | x=-1.01255555555555 | | 7/5x-10=3 | | 6[x+4(2-x)]=3x+1 | | 5t^2+2t+0.1=0 | | 3x+7-5(x+1)=5x+7 | | 4/3(3.14)(11)3 | | P=pr^2+prs | | .07x=1400 | | 0.7x=1400 | | (11b-2)-5(2b+1)=-7 | | 5+20x=y | | 10y/7=14 | | 77760+0.10x+0.15x=x | | 10y=14*7 | | 0.10x+0.15x=x | | 2.7+3w=6-8w | | h=3+5t-5y^2 | | -n=-120 | | 10-10d+3=6d+4 | | 315/5= | | 6x^2y+12xy^2= | | 5x+2=-3x+7 | | 21x+121=-104 | | (X+1)(x-1)+x(x-1)=x^2 | | 4=3x^2-6x | | X^2-34x=78 | | -2p(2-q/2) | | 5x=100/2 | | x^2-4x/x-2=14-9x/x-2 |

Equations solver categories